2020
DOI: 10.1007/s11783-020-1336-8
|View full text |Cite
|
Sign up to set email alerts
|

The source and transport of bioaerosols in the air: A review

Abstract: Recent pandemic outbreak of the corona-virus disease 2019 (COVID-19) has raised widespread concerns about the importance of the bioaerosols. They are atmospheric aerosol particles of biological origins, mainly including bacteria, fungi, viruses, pollen, and cell debris. Bioaerosols can exert a substantial impact on ecosystems, climate change, air quality, and public health. Here, we review several relevant topics on bioaerosols, including sampling and detection techniques, characterization, effects on health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 120 publications
0
50
0
Order By: Relevance
“…Bioaerosol exposure derived by natural and anthropogenic sources has assumed greater importance in recent years [5]. Exposure to pollen biocomponents can be responsible for several health effects and knowledge of their levels, interactions with other components, modification in relationship with the presence and absence of occupants, as well as their diffusion in several environments can be useful in improving the evaluation and management of this biological risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioaerosol exposure derived by natural and anthropogenic sources has assumed greater importance in recent years [5]. Exposure to pollen biocomponents can be responsible for several health effects and knowledge of their levels, interactions with other components, modification in relationship with the presence and absence of occupants, as well as their diffusion in several environments can be useful in improving the evaluation and management of this biological risk.…”
Section: Discussionmentioning
confidence: 99%
“…From a biological, ecological and agricultural point of view, pollen is indispensable. However, from a human health perspective, pollen can be seen as an aerobiological pollutant mainly responsible for respiratory and allergic diseases [1][2][3][4][5][6] and has been recently associated with different health effects. Lung function, seasonality of flu-like illnesses, SARS-CoV-2 infection rates, and occurrence of several cancers have been put related to airborne pollen variations [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We also know that the spread of mold fungi is influenced by atmospheric conditions, especially relative humidity, wind speed, temperature, and insolation [18,24,52]. Our research also attempted to assess the impact of meteorological conditions on the presence of mold and yeast-like fungi in the seaside air of the towns of Hel, Puck, Gdynia, Sopot, and Gda ńsk-Brzeźno.…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins, by-products of fungal metabolism, which may cause pain, dizziness, or immunosuppression, are an additional threat related to the presence of mold fungi in the air [22]. Previous studies have shown that fungal spores, bacteria, their endotoxins, and even viruses can be transported over long distances, where meteorological factors play a large role [3,23,24]. It is also known that in the coastal region, the strength and direction of the wind are the greatest factors influencing the microbiological quality of air [15,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Bioaerosols within the diameter of 100 µm mainly refer to bacteria, viruses, fungi, and some microbial fragments suspended in the air [ 1 , 2 , 3 ]. The size of bioaerosols containing fungi, bacteria, and viruses generally range from 1 to 30 μm, from 0.25 to 8 μm and less than 0.3 μm, respectively [ 4 , 5 ]. According to the report from the World Health Organization, lower respiratory infections remained the world’s most deadly communicable disease and were ranked as the 4th leading cause of death, resulting in 2.6 million deaths in 2019 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%